Negotiations over parental care: a test of alternative hypotheses in the clown anemonefish. (7th August 2021) - Barbasch, Tina A; Branconi, Rebecca; Francis, Robin; Pacaro, Madison; Srinivasan, Maya; Jones, Geoffrey P; Buston, Peter M
Abstract: In species with biparental care, conflict arises over how much each parent provides to their offspring because both parents benefit from shifting the burden of care to the other. Here, we tested alternative hypotheses for how parents will negotiate offspring care using a wild population of clownfish ( Amphiprion percula ). We experimentally handicapped parents by fin-clipping the female in 23 groups, the male in 23 groups, and neither parent in 23 groups and measured changes in indicators of female, male, and pair effort in response to handicapping. First, we found that handicapping resulted in a decrease in the number of eggs laid by fin-clipped females and a decrease in the amount of parental care by fin-clipped males. Second, contrary to predictions, female effort did not change in response to the male being handicapped, or vice versa. Finally, the number of embryos that matured to hatching, an indicator of pair effort, was not influenced by the manipulation, suggesting that although the handicap was effective, clownfish do not face the predicted "cost to conflict" when one parent is handicapped. Together, these results test the generality of theoretical predictions and uncover novel questions about whether and how negotiations operate in systems where interests are aligned. Abstract : Clownfish parents pay no heed to current theories concerning how they should negotiate their efforts. A suite of models predict how parents should respond to each other's efforts and care for their offspring. However, a test of these models in clownfish, involving handicapping one parent and observing response of the other, revealed that parents seemingly do not respond to each other. This should stimulate new theory on the factors that influence negotiations over bi-parental care.